Research on the performance of MAC protocols in UWB-ad hoc system - YUE Ran1; WU Wei-qiang2; ZHANG Qin-yu 2; ZHANG Nai-tong 1 (Tongxin xuebao)
In general,QoS guarantee is the basic element for a communication system in the real world.Accordingly,the relationship between transmission power and SINR was investigated,as well as the relationship between SINR and data rate.And different QoS requirements correspond to various applications.Then a MAC protocol,named TDQG was presented based on TH-UWB-ad hoc system,which can guarantee QoS requirements in term of material traffics.TDQG reserves resource to the potential links to accommodate the distributed character of ad hoc network,and dynamically assigns the resource to make the best of it.A mass of simulation results gave more proves to the superiority of TDQG in UWB-ad hoc system.